Analisis Peran Media Papan Display untuk Meningkatkan Pemahaman Materi IPS pada Siswa Kelas IV Sekolah Dasar Berdasarkan Kajian Kepustakaan - Wardah Salwa Aqilah (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Sorong, 2019)
This literature review examines the role of display board media in enhancing the understanding of social studies material among fourth-grade elementary school students. The background of this study is rooted in the challenges faced by students in comprehending abstract social studies concepts, which require concrete and visual learning media. The purpose of this research is to analyze how display board media can improve students' understanding of social studies material based on literature review. The method employed is a library research approach, collecting data from journals and books published from 2021 onwards. Data were analyzed through content analysis techniques to identify themes and patterns related to the effectiveness of display board media. The results indicate that display board media play a significant role in improving students' understanding through three main mechanisms: providing concrete visualization of abstract concepts, facilitating active and interactive learning, and increasing student motivation and attention. Display boards effectively present maps, timelines, cultural images, and social structures that support the comprehension of spatial, temporal, and social relationship concepts. The conclusion of this study emphasizes that display board media are relevant and effective learning tools for teaching social studies in elementary schools, particularly for fourth-grade students who are in the concrete operational stage. Recommendations are provided for teachers to optimize the use of display board media by integrating interactive elements and adjusting content to students' cognitive development.